High intensity laser-plasma sources of ions - Physics and future applications - Krushelnick, K; Clark, E; Beg, F; Dangor, A; Najmudin, Z; Norreys, P; Wei, M; Zepf, M (2005)
The interaction of high intensity laser pulses with plasmas is an efficient source of megaelectronvolt ions. Recent observations of the production of directional energetic ion 'beams' from the front and rear surfaces of thin foil targets upon irradiation by intense laser pulses have prompted a renewed interest into research in this area. In addition, other recent observations have shown that high energy ions can be observed from intense laser interaction with low density plasma as a result of ponderomotive shock acceleration. The source characteristics and acceleration mechanisms for these ions have been extensively investigated, and there have also been a number of proposed applications for these ion beams, such as for injectors into subsequent conventional acceleration stages, for medicine, for probing of dense plasmas and for inertial confinement fusion experiments. © 2005 IOP Publishing Ltd.